Kebijakan Pembaharuan Konsep Perzinahan Pasal 411 Undang-Undang Nomor 1 Tahun 2023 KUHP Indonesia - Mashendra Mashendra; Jennifer Corrin; Auliah Andika Rukmana (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
The current Dutch colonial Kitab Undang-Undang Hukum Pidana (KUHP) needs to be replaced with an updated Indonesian Criminal Code. Legal scholars, especially those specializing in criminal law, have long debated the overhaul, reformulation, modification, and even reformation of the Criminal Code to conform to the guiding principles of the Indonesian nation as a whole and this discussion has been ongoing for quite some time. This research intends to evaluate the policy basis of the expansion of the definition of adultery and the values protected from the expansion as stipulated in Article 411 of Law Number 1 Year 2023 on the Criminal Code This research is a descriptive study that uses a normative legal approach. Secondary data and document study are used in data collection. A qualitative approach was used to analyze the data. The research findings show that the criminal policy perspective is the basis for the expansion policy that contains a definition of the offense of adultery that is problematic as a policy because it does not reflect the principles that guide Indonesian society and the nation as a whole. With the way the article is currently written, for every person who has sexual intercourse with anyone as long as he is not his husband or wife and does not regulate the imposition of punishment for convicts who are single. The findings in this study highlight the importance of policy implementation of expanding the concept of adultery to ensure that justice is maintained and equal protection is given to all parties accused without sufficient evidence.